Prevention or early cure of type 1 diabetes by intranasal administration of gliadin in NOD mice - Funda, David P; Fundova, Petra; Hansen, Axel Kornerup; Buschard, Karsten (PloS one, 2014)
Induction of long-term tolerance to β-cell autoantigens has been investigated both in animal models and in human type 1 diabetes (T1D) in order to prevent the disease. As regards external compounds, the dietary plant protein fraction has been associated with high penetrance of the disease, whereas gluten-free diets prevent T1D in animal models. Herewith we investigated whether intranasal (i.n.) administration of gliadin or gluten may arrest the diabetogenic process. I.n. administration of gliadin to 4-week-old NOD mice significantly reduced the diabetes incidence. Similarly, the insulitis was lowered. Intranasal gliadin also rescued a fraction of prediabetic 13-week-old NOD mice from progressing to clinical onset of diabetes compared to OVA-treated controls. Vaccination with i.n. gliadin led to an induction of CD4(+)Foxp3(+) T cells and even more significant induction of γδ T cells in mucosal, but not in non-mucosal lymphoid compartments. This prevention strategy was characterized by an increased proportion of IL-10 and a decreased proportion of IL-2, IL-4 and IFN-γ-positive CD4(+)Foxp3(+) T cells, and IFN-γ-positive γδ T cells, preferentially in mucosal lymphoid organs. In conclusion, i.n. vaccination with gliadin, an environmental antigen with possible etiological influence in T1D, may represent a novel, safer strategy for prevention or even early cure of T1D.
Keywords: Immunity, Mucosal; počet lymfocytů; Animals; Female; Lymphocyte Count; Cytokines; gluteny; Lymphoid Tissue; aplikace intranazální; ženské pohlaví; Gliadin; cytokiny; lymfoidní tkáň; lidé; myši inbrední NOD; Administration, Intranasal; forkhead transkripční faktory; Humans; Diabetes Mellitus, Type 1; Forkhead Transcription Factors; Mice, Inbred NOD; Glutens; CD4-Positive T-Lymphocytes; zvířata; slizniční imunita; gliadin; diabetes mellitus 1. typu; CD4-pozitivní T-lymfocyty